2014
DOI: 10.15274/nrj-2014-10013
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Total Obliteration in Endovascular Treatment of Cerebral Arteriovenous Malformations

Abstract: SUMMARY -Endovascular therapy is a therapeutic option that can achieve total obliteration of cerebral arteriovenous malformations (AVMs (OR: 50.9; 0; P = 0.000), and opposing factors,(3)(4)(5)(6)4; P = 0.002) and afferences of more than two vessels of the Willis polygon (OR: 7.0; P = 0.038). An AVM diameter smaller than 3 cm is a predictive factor of total obliteration. Total postembolization obliteration persisted in 100% of the cases after 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…Multivariate analysis revealed that factors associated with incomplete obliteration in the PCT group were nidus size >3 cm and deep location. Similar findings were published by Jordan and collaborators who demonstrated a nidus size of 30–60 mm is associated with incomplete obliteration ( 19 ). Van Rooij et al reported a nidus size of 10–30 mm as a factor associated with complete obliteration ( 6 ).…”
Section: Discussionsupporting
confidence: 90%
“…Multivariate analysis revealed that factors associated with incomplete obliteration in the PCT group were nidus size >3 cm and deep location. Similar findings were published by Jordan and collaborators who demonstrated a nidus size of 30–60 mm is associated with incomplete obliteration ( 19 ). Van Rooij et al reported a nidus size of 10–30 mm as a factor associated with complete obliteration ( 6 ).…”
Section: Discussionsupporting
confidence: 90%
“…It was soon realized, however, that complete elimination could not be routinely achieved. The introduction of Onyx, offering more controllable intranidal dispersion, did not change the picture fundamentally, achieving complete elimination in maximally 50 % [5,13,16]. Embolization also remained associated with substantial complications despite technical advances.…”
mentioning
confidence: 99%
“…The clinical, demographic, morphological and general characteristics of the treatment for AVMs in the studied series were reported in previous papers 22,23 .…”
Section: Resultsmentioning
confidence: 95%